Study of natural and traffic-producing turbulences analysing full-scale data from four street canyons - Mazzeo, Nicolas Antonio (2011)
Parameters related with natural and traffic producing turbulences are estimated for four street canyons considering all wind directions. Available data include air pollution concentrations measured in Göttinger Strasse (Hannover, Germany), Schildhornstrasse (Berlin, Germany), Jagtvej (Copenhagen, Denmark) and Hornsgatan (Stockholm, Sweden), background pollution, wind speed and direction measured on the roof of a nearby building and information of traffic flow. Results show that coefficients a and b, related to natural- and traffic- produced turbulences, vary with wind direction. The variation of critical wind speed with traffic density and wind direction is also studied for each street canyon.